Management of disabilities athletes sport branch sitting volleyball - Ismail, Taufik; Sugiyanto, .; Purnama, Sapta Kunta (Quality in Sport, 2021)
This study aims to determine the management of athletes with disabilities in sitting volleyball. The research method used is an interpretive study research on the Coaching Activities of Athletes with Disabilities in the Indonesian National Pelatnas Volleyball Sports Branch in Surakarta. The population of this study were athletes, coaches and administrators of the Indonesian NPC. The data collection techniques used by the researcher are active observation, interviews, and documentation analysis. In this study, researchers used two triangulation techniques, namely data triangulation and method triangulation. The data validity technique used triangulation technique. Data analysis was carried out in four stages, namely: the data collection stage, the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results showed that the athletes in the seated volleyball sport were quite good. Communication between athletes, administrators and coaches is very good because they always approach each other emotionally. Coaches in coaching athletes with disabilities in the Indonesian seated volleyball sport must have a minimum national license. The condition of good facilities and infrastructure will provide convenience in the process of coaching athletes with disabilities in sitting volleyball. The funding system for the coaching of athletes with disabilities in sitting volleyball from the Ministry of Youth and Sports as a whole with the financial system set for coaching athletes with disabilities in sitting volleyball from the APBN budget. The implementation of the training method for coaching athletes with disabilities in the seated volleyball sport is well programmed. This can be seen from the preparation of a written training program, the training schedule is in accordance with the national level training schedule, the division of short-term periodization, medium-term periodization, and long-term periodization. Keywords: Management, Athletes Disabilities, Sitting Volleyball